Association Internationale Des Soci�t�s De Microbiologie
DOI: 10.1159/000389848
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vaccinia Hyperimmune Gammaglobulin in the Prophylaxis of Smallpox

Abstract: This paper records an attempt to assess the prophylactic value of immune gammaglobulin, prepared from the serum of recently vaccinated adults, in the protection of close contacts of smallpox in Madras. The results serve to confirm findings of a previous study made in Madras in 1953, and show that the incidence of smallpox in close contacts given immune gamma-globulin prophylactically was about a quarter of that in the control contacts who received no such passive immunization-a statistically significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 1 publication
1
48
0
1
Order By: Relevance
“…Since Abs can be protective against smallpox (8,20), memory B cells are likely to be important players in human immunity to smallpox, both by their ability to rapidly respond to infection with an anamnestic Ab response and by their potential ability to replenish long-lived plasma cells to maintain long-term Ab levels. VV-specific memory T cells are also likely to be critical components of the vaccine-mediated protection against smallpox virus (8), and the smallpox vaccine is known to elicit T cell responses (13,16,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Since Abs can be protective against smallpox (8,20), memory B cells are likely to be important players in human immunity to smallpox, both by their ability to rapidly respond to infection with an anamnestic Ab response and by their potential ability to replenish long-lived plasma cells to maintain long-term Ab levels. VV-specific memory T cells are also likely to be critical components of the vaccine-mediated protection against smallpox virus (8), and the smallpox vaccine is known to elicit T cell responses (13,16,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Both cellular and humoral immunity (virus-specific antibody) have been thought to play a role in protection against orthopoxviruses. This view is based in part on experience with poor control of vaccinia virus infection in individuals with either humoral or cellular immune defects (16), in part on the known efficacy of vaccinia-immune globulin (17), and in part on studies in mice showing a key role for IFN-␥, probably derived from T cells, in control of vaccinia and ectromelia virus infections (18)(19)(20)(21). Several studies have mapped proteins important for the elicitation of neutralizing antibodies (22)(23)(24)(25)(26)(27).…”
Section: T He Licensed Smallpox Vaccine Currently In Use In the Unitedmentioning
confidence: 99%
“…Passively transferred antibody has been successful in preventing or modifying disease in smallpox contacts (Pierce, Melville, Downie & Duckworth, 1958;Kempe, 1960;Kempe et al 1969) but the vaccination reactions of people with antibody deficiencies (Kempe, 1960;Medical Research Council Working-Party, 1969;FulgiDiti et al 1968), deficiencies in cell-mediated immunity or lack of both types of response (Kempe, 1960;Medical Research Council Working-Party, 1969;Fulginiti et at. 1966) have indicated that the cell-mediated response is vital for the elimination of infection.…”
Section: Introductionmentioning
confidence: 99%